1965
DOI: 10.1021/ja01084a020
|View full text |Cite
|
Sign up to set email alerts
|

New Aspects of the Hofmann-Loeffler N-Chloramine Rearrangement in Acetic Acid

Abstract: bonate solution, and filtration and acidification of the bicarbonate extract gave a yellow precipitate. Recrystallization from ethanol and from methyl ethyl ketone-hexane afforded 1.0 g. of yellow and red crystals of the presumed 2-anthrylglyoxylic acid, m.p. 24Ck 284" dec., which was not purified further.A solution of 0.5 g. of the glyoxylic acid in 0.5 ml. of N,N-dimethyl-p-toluidine was heated gently until decarboxylation commenced. The temperature was raised from 150 to 190" over 0.5 hr. until gas evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1970
1970
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…CS σ‐bond is 56.55 Kcal/mol, CN σ‐bond is 64.03 Kcal/mol, and CC σ‐bond is 72.34 kcal/mol 78. While the primary requirement for the synthesis of polymers with narrow molecular weight distributions is achieved, the quantitative initiation observed for the case of arenesulfonyl radicals9 cannot be matched by the N‐centered radicals for at least three reasons: their increased tendency to undergo dimerization,79, 80 their higher electrophilicity,80, 81 and their side reactions 82–92. The possible side reactions of N‐centered radicals are illustrated in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…CS σ‐bond is 56.55 Kcal/mol, CN σ‐bond is 64.03 Kcal/mol, and CC σ‐bond is 72.34 kcal/mol 78. While the primary requirement for the synthesis of polymers with narrow molecular weight distributions is achieved, the quantitative initiation observed for the case of arenesulfonyl radicals9 cannot be matched by the N‐centered radicals for at least three reasons: their increased tendency to undergo dimerization,79, 80 their higher electrophilicity,80, 81 and their side reactions 82–92. The possible side reactions of N‐centered radicals are illustrated in Scheme .…”
Section: Resultsmentioning
confidence: 99%
“…The chlorammonium ion results from reaction of chloramines in acidic solutions (94) yielding a chlorine atom [Eq. (16) …”
Section: Chlorination Mechanisms Of Organic Compoundsmentioning
confidence: 99%
“…-3Previous workers have reported that the ;ate of the immediately prior to, or during the course of, intran~olecular (Hoffman-Loffler) reaction is increased reaction with the other radical. It is unfortunate (18) and decreased (19) by an increase in solvent acidity. that the absolute rate constants could not be However, in neither piece of uork was the rate of initiation in the different solvents estimated.…”
Section: Absolute Rate Constantsmentioning
confidence: 99%
“…They suggested that this resulted from the fact that the self-reaction of two protonated, positively charged nitrogen radicals was far slower than the self-reaction of the neutral radicals which were assumed to be [he species actually responsible for termination. However, as Neale and Walsh have pointed out (19), this requires that the basicity of the amino radical be less than that of the corresponding chloroamine, since the latter is protonated even in the most weakly acidic solutions used. The available evidence (19,23) suggests that the radical is a much stronger base than the chloroamine.…”
mentioning
confidence: 99%
See 1 more Smart Citation